Pentecostal mission and global Christianity : an Edinburgh centenary reader - Lee, Younghoon, 1954-; Ma, Wonsuk; Lee, Kuewon (Regnum studies in mission., 2018)
Twenty six studies on Pentecostal mission previously published in various volumes in the Regnum Edinburgh centenary series.